IMPLEMENTING LISTEN AND IMITATE TECHNIQUE TO IMPROVE PRONUNCIATION SKILL - Hasriani; Anwar; Mujahidah (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
This study aims to find out the improvement of non-native English students in pronunciation by using Listen and Imitate technique. This technique was selected to enhance the students? ability in pronouncing different sounds from their native language. Listening then imitating the sounds repeatedly will ease the students pronounced them perfectly. This research was quantitative which employed pre-experimental research with one group pretest-posttest design. The result of the pre test and post test was then compared to see the improvement of the Student?s pronunciation after the treatment using Listen and Imitate Technique. This study found out the use of listen and imitate technique was able to improve students? pronunciation skill significantly. This study also provides a set of suggestion to overcome the students? pronunciation problem.